Competing in the Global Economy : An Investment Climate Assessment for Uganda - Cotton, Linda (World Bank and International Finance Corporation, Washington, DC, 2013)
Uganda's economic growth since the late 1980s has resulted largely from restoring and rehabilitating the country's productive capacity. Going forward, growth will need to come increasingly from new investments or new activities. That will require more investment, more intensive acquisition of know-how, and more complex collaboration between local and foreign partners. It will also require a far greater role for private sector investment. While Uganda has benefited enormously from development assistance for almost two decades, foreign aid may decline in the next decade. Indeed, Uganda must accelerate private sector investment and growth if it is to achieve the goals set out in its Poverty Eradication Action Plan. To reduce the poverty rate to 10 percent by 2017, GDP growth will have to exceed 7 percent a year, requiring an investment rate of 30 percent or more of GDP. Attaining these targets will be feasible only with reforms to promote private investment.